Smoking cessation care among patients with head and neck cancer: a systematic review. Issue 9 (20th September 2016) - McCarter, Kristen; Martínez, Úrsula; Britton, Ben; Baker, Amanda; Bonevski, Billie; Carter, Gregory; Beck, Alison; Wratten, Chris; Guillaumier, Ashleigh; Halpin, Sean A; Wolfenden, Luke
Abstract : Objective: To examine the effectiveness of smoking cessation interventions in improving cessation rates and smoking related behaviour in patients with head and neck cancer (HNC). Design: A systematic review of randomised and non-randomised controlled trials. Methods: We searched the following data sources: CENTRAL in the Cochrane Library, MEDLINE, EMBASE, PsycINFO and CINAHL up to February 2016. A search of reference lists of included studies and Google Scholar (first 200 citations published online between 2000 and February 2016) was also undertaken. The methodological quality of included studies was assessed using the Effective Public Health Practice Project Quality Assessment Tool (EPHPP). 2 study authors independently screened and extracted data with disagreements resolved via consensus. Results: Of the 5167 studies identified, 3 were eligible and included in the review. Trial designs of included studies were 2 randomised controlled trials and 1 non-randomised controlled trial. 2 studies received a weak methodological rating and 1 received a moderate methodological rating. The trials examine the impact of the following interventions: (1) nurse delivered cognitive–behaviour therapy (CBT) via telephone and accompanied by a workbook, combined with pharmacotherapy; (2) nurse and physician brief advice to quit and information booklets combined with pharmacotherapy; and (3) surgeon delivered enhanced advice to quit smoking augmented by booster sessions. Only the trial of the nurse delivered CBT and pharmacotherapy reported significant increases in smoking cessation rates. 1 study measured quit attempts and the other assessed consumption of cigarettes per day and readiness to change. There was no significant improvement in quit attempts or cigarettes smoked per day among patients in the intervention groups, relative to control. Conclusions: There are very few studies evaluating the effectiveness of smoking cessation interventions that report results specific to the HNC population. The 3 trials identified reported equivocal findings. Extended CBT counselling coupled with pharmacotherapy may be effective. Trial registration number: CRD42016016421.